Calculation of macroparticle flow in filtered vacuum ARC plasma systems - Aksyonov, D.S. (Вопросы атомной науки и техники, 2012)
Model of macroparticle behavior inside plasma guiding channels of vacuum arc systems and program for calculation of macroparticle flow in plasma filters (separators) used in vacuum arc film deposition are described. Several magnetic filters have been modeled to compare calculated and experimental data. The capability of the program to optimize filters is demonstrated on example of straight filter. The high compliance degree of calculated and experimental data is shown. Представлены модель, алгоритм работы и возможности программы для расчёта и оптимизации плазменных фильтров (сепараторов), используемых в вакуумно-дуговом осаждении покрытий. Промоделировано несколько магнитных фильтров для сопоставления расчётных и экспериментальных данных. Продемонстрирована возможность оптимизации одного из фильтров с помощью разработанной программы. Показана высокая степень соответствия расчётных данных экспериментальным. Наведено модель, алгоритм роботи та можливості програми для розрахунку та оптимізації плазмових фільтрів (сепараторів), які використовуються у вакуумно-дуговому осадженні покриттів. Промодельовані декілька магнітних фільтрів для порівняння розрахункових та експериментальних даних. Продемонстрована можливість оптимізації одного з фільтрів за допомогою розробленої програми. Показано високий ступінь відповідності розрахункових даних експериментальним.